2016
DOI: 10.1371/journal.pone.0149229
|View full text |Cite
|
Sign up to set email alerts
|

Major Transcriptome Changes Accompany the Growth of Pseudomonas aeruginosa in Blood from Patients with Severe Thermal Injuries

Abstract: Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen that causes serious infections in immunocompromised hosts including severely burned patients. After multiplying within the burn wound, P. aeruginosa translocate into the bloodstream causing bacterial sepsis frequently leading to organ dysfunction and septic shock. Although the pathogenesis of P. aeruginosa infection of thermally-injured wounds has been extensively analyzed, little is known regarding the ability of P. aeruginosa to adapt and survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 73 publications
(98 reference statements)
1
52
0
Order By: Relevance
“…Previous study of L. plantarum found several global regulators of gene expression, such as CtsR, HrcA, and CcpA, which upregulate the expression of various gene networks in response to stressors such as acidic or alkaline environments, high temperatures, and caloric restriction [36,37]. These studies have indicated that, in response to stressors, L. plantarum changes its energy metabolism as well as its production of fatty acids and exopolysaccharides incorporated into biofilms [38,39]. Our data agrees with these observations, demonstrating changes in oligosaccharide and fatty acid transports between attached (original place of biofilm formation) and detached phases after 24 h. in flow culture.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous study of L. plantarum found several global regulators of gene expression, such as CtsR, HrcA, and CcpA, which upregulate the expression of various gene networks in response to stressors such as acidic or alkaline environments, high temperatures, and caloric restriction [36,37]. These studies have indicated that, in response to stressors, L. plantarum changes its energy metabolism as well as its production of fatty acids and exopolysaccharides incorporated into biofilms [38,39]. Our data agrees with these observations, demonstrating changes in oligosaccharide and fatty acid transports between attached (original place of biofilm formation) and detached phases after 24 h. in flow culture.…”
Section: Discussionmentioning
confidence: 96%
“…Biofilm was collected separately from A and D phases after 24 (n = 3 each) and 48 h. (n = 3 each) of culture flash frozen in liquid nitrogen and stored at − 80°C for future analyses. RNA was extracted, using TRIzolℱ reagent [37] and Next Generation sequencing (NGS) was performed as previously described [38], utilizing the Illumina MiSeq platform (San Diego, CA). We compared whole genome expression of biofilms from the A and D phases at the bottom of the fermenter as validation of biofilm formation/maturation capacities as well as of biofilm growth by measuring both bacterial biomass from the spatula and from the bottom of the microfermenter in a time-dependent manner (24 and 48 h.).…”
Section: Rna Extraction and Sequencingmentioning
confidence: 99%
“…P . aeruginosa utilizes numerous cell-associated and extracellular virulence factors including lipopolysaccharides, flagella, pili, exotoxin A, elastases, proteases, type III secretion effectors (ExoS, ExoT, ExoY, and ExoU), pyocyanin, catalase, alginate, and LasR/RhlR quorum-sensing molecules [15,16]. However, critical factors that play a key role in penetration through the Caco-2 epithelial barrier are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies, the pathogenesis of P. aeruginosa infection during trauma-induced sepsis has not been defined. In an attempt to understand bacterial pathogenesis during sepsis following burn injury, we recently initiated a new approach, in which we grew P. aeruginosa in whole blood and examined the changes in expression of the transcriptome (13). The growth of P. aeruginosa in whole blood from severely burned patients significantly enhanced the expression of specific sets of virulence genes, such as iron-regulated genes, quorum sensing-related genes, and type III secretion genes, as well as numerous previously uncharacterized genes, compared with their expression when P. aeruginosa was grown in whole blood from healthy volunteers (13).…”
mentioning
confidence: 99%
“…In an attempt to understand bacterial pathogenesis during sepsis following burn injury, we recently initiated a new approach, in which we grew P. aeruginosa in whole blood and examined the changes in expression of the transcriptome (13). The growth of P. aeruginosa in whole blood from severely burned patients significantly enhanced the expression of specific sets of virulence genes, such as iron-regulated genes, quorum sensing-related genes, and type III secretion genes, as well as numerous previously uncharacterized genes, compared with their expression when P. aeruginosa was grown in whole blood from healthy volunteers (13). One of the genes whose expression was significantly enhanced upon the growth of P. aeruginosa strain UCBPP_PA14 (PA14) in whole blood from severely burned patients was hepP, a previously uncharacterized gene encoding a heparinase enzyme.…”
mentioning
confidence: 99%